2008
DOI: 10.3324/haematol.13204
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of peripheral blood stem cells in myeloma with either pegfilgrastim or filgrastim following chemotherapy

Abstract: Quality and quantity of mobilized peripheral blood stem cells determine the safety of tandem autologous transplants in myeloma. Using the same mobilization chemotherapy with DT-PACE in two consecutive protocols, robustness of stem cell collection and rapidity of engraftment after transplantation were assessed. We employed either twice a day filgrastim versus two doses of pegfilgrastim. Advantages of pegfilgrastim were: (i) a higher percentage of patients collected 15x10 6 /kg in the first three days (p<0.001);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…An additional advantage compared with the use of conventional G-CSF is the faster neutrophil recovery after pegfilgrastim, which may be associated with a reduced risk of infection-related complications during neutropenia. Another benefit of cytotoxic stem cell mobilization with pegfilgrastim is the reduction of the number of injections required from 11 (median; range: 8-15) to 1 injection in our study, and from a median number of 26 to 2 injections in the study of Tricot et al, 23 which increases patient comfort and convenience.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…An additional advantage compared with the use of conventional G-CSF is the faster neutrophil recovery after pegfilgrastim, which may be associated with a reduced risk of infection-related complications during neutropenia. Another benefit of cytotoxic stem cell mobilization with pegfilgrastim is the reduction of the number of injections required from 11 (median; range: 8-15) to 1 injection in our study, and from a median number of 26 to 2 injections in the study of Tricot et al, 23 which increases patient comfort and convenience.…”
Section: Introductionmentioning
confidence: 82%
“…On the other hand, it has been shown that the pegylation of G-CSF not only enhances serum half-life, and thus receptor occupancy, but also alters the cellular trafficking of G-CSF to enhance G-CSF receptor stimulation at a cellular level. 38 The first clinical evidence for this phenomenon has recently been presented by Tricot et al 23 In their double transplant study on 237 myeloma patients in two consecutive protocols at the University of Arkansas, they found a significantly faster recovery of neutrophils and platelets after transplantation of pegfilgrastim-mobilized haematopoietic stem cell grafts in comparison with conventional G-CSF. The advantage of pegfilgrastim-mobilized cells disappeared during the second transplant when the number of reinfused CD34 þ cells was increased from about 4 million to more than 6 million/kg patient weight.…”
Section: Different Biological and Functional Properties Of Haematopoimentioning
confidence: 99%
See 1 more Smart Citation
“…Another group reported superior efficacy to filgrastim plus chemotherapy mobilization when two doses of pegfilgrastim were administered, at day þ 6 and day þ 13 post aggressive salvage chemotherapy in multiple myeloma. 22 In aggressive lymphoma post ESHAP (etoposide, methylprednisolone, cytarabine and cisplatin) chemotherapy pegfilgrastim 6 mg has demonstrated similar mobilization efficacy to a control group mobilized with filgrastim post ESHAP. 23 The adverse event profile of pegfilgrastim mobilization is very similar to filgrastim mobilization, including bone pain, skin reaction and rare reports of splenic rupture.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some groups have observed best mobilization results with pegylated G-CSF (pegfilgrastim) compared with standard G-CSF not pegylated. 18,19 Recently, this method has been evaluated by Tricot et al 19 This study showed that PBSC post-chemotherapy is feasible and similarly effective with pegfilgrastim and filgrastim, with the advantages of greater ease and cost-effectiveness with pegfilgrastim. For these authors, pegfilgrastim may become the standard growth factor to be used for stem cell mobilization with or without chemotherapy.…”
mentioning
confidence: 99%